2015
DOI: 10.3102/0002831215596413
|View full text |Cite
|
Sign up to set email alerts
|

Gifted and Maladjusted? Implicit Attitudes and Automatic Associations Related to Gifted Children

Abstract: The disharmony hypothesis (DH) states that high intelligence comes at a cost to the gifted, resulting in adjustment problems. We investigated whether there is a gifted stereotype that falls in line with the DH and affects attitudes toward gifted students. Preservice teachers (N = 182) worked on single-target association tests and affective priming tasks. High intelligence was more strongly associated with gifted than with average-ability students. Adjustment problems were more strongly associated with gifted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 69 publications
(101 reference statements)
2
58
2
4
Order By: Relevance
“…However, gifted male and female students were perceived as equally more maladjusted compared to average-ability students. This finding is in contrast to the findings by Preckel et al (2015) who found that pre-service teachers associated gifted male students most strongly with adjustment problems. However, Preckel et al (2015) investigated implicit stereotypes, that is, beliefs of which people do not need to be aware, whereas we assessed explicit stereotypes, that is, beliefs that people consciously endorse.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, gifted male and female students were perceived as equally more maladjusted compared to average-ability students. This finding is in contrast to the findings by Preckel et al (2015) who found that pre-service teachers associated gifted male students most strongly with adjustment problems. However, Preckel et al (2015) investigated implicit stereotypes, that is, beliefs of which people do not need to be aware, whereas we assessed explicit stereotypes, that is, beliefs that people consciously endorse.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is in contrast to the findings by Preckel et al (2015) who found that pre-service teachers associated gifted male students most strongly with adjustment problems. However, Preckel et al (2015) investigated implicit stereotypes, that is, beliefs of which people do not need to be aware, whereas we assessed explicit stereotypes, that is, beliefs that people consciously endorse. Explicit and implicit beliefs can be unrelated to each other (e.g., Gawronski & Bodenhausen, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…If elevated IQ levels are, in fact, associated with negative biological and/or psycho-social characteristics, then it is possible that, as a group, the participants in this investigation were influenced by such considerations. Alternatively, the participants may have appealed to stereotypes relevant to those with very elevated levels of intelligence (Baudson & Preckel, 2013;Preckel, Baudson, Krolak-Schwerdt, & Glock, 2015).…”
Section: Percentile Levelsmentioning
confidence: 99%